2008
DOI: 10.2495/wm080521
|View full text |Cite
|
Sign up to set email alerts
|

Chemical recycling of PET by alkaline hydrolysis in the presence of quaternary phosphonium and ammonium salts as phase transfer catalysts

Abstract: Chemical or tertiary recycling of waste polymers including PET, poly(ethylene terephthalate), is the only method according to the principles of Sustainable Development, since it leads to the formation of the raw materials (monomers) from which the polymer is made of. This work has been focused on the determination of the kinetics of the depolymerisation of PET by means of alkaline hydrolysis and on the identification of the catalytic behaviour, if any, of a series of phosphonium and ammonium salts as phase tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…The effect of quaternary ammonium salt as a phase-transfer catalyst for the microwave depolymerization of PET waste bottles had been studied by Khalaf et al The PET was depolymerized to TPA and EG by hydrolysis process using 10% NaOH and ammonium salt as phase-transfer catalyst under microwave irradiation, which PET conversion was up to 99% [ 133 ]. López-Fonseca et al presented that tributylhexadecylphosphonium bromide was found to be the most effective catalyst to conduct the PET alkaline hydrolysis (>90% conversion) at 80 °C and 1.5 h [ 134 ]. Kosmidis et al presented the kinetics of PET alkaline hydrolysis by phase-transfer catalysis [ 135 ].…”
Section: The Recent Development Of Pet Chemical Recyclingmentioning
confidence: 99%
“…The effect of quaternary ammonium salt as a phase-transfer catalyst for the microwave depolymerization of PET waste bottles had been studied by Khalaf et al The PET was depolymerized to TPA and EG by hydrolysis process using 10% NaOH and ammonium salt as phase-transfer catalyst under microwave irradiation, which PET conversion was up to 99% [ 133 ]. López-Fonseca et al presented that tributylhexadecylphosphonium bromide was found to be the most effective catalyst to conduct the PET alkaline hydrolysis (>90% conversion) at 80 °C and 1.5 h [ 134 ]. Kosmidis et al presented the kinetics of PET alkaline hydrolysis by phase-transfer catalysis [ 135 ].…”
Section: The Recent Development Of Pet Chemical Recyclingmentioning
confidence: 99%
“…98 To reproduce pure TPA, Karayannidis Chemical recycling of waste PET through hydrolytic depolymerization with aqueous NaOH solution in the presence of the various phase transfer catalysts was performed to investigate the catalytic behavior and the underlying kinetic model. [104][105][106] Thus, a series of nine divergent phosphonium and ammonium salts as phase transfer catalysts were tested to find which was the most effective catalyst.…”
Section: Neutral Hydrolysismentioning
confidence: 99%
“…Catalyst can also be used to conduct alkaline hydrolysis of PET in low temperatures (below 100 °C) and atmospheric pressure. This catalyst is known as the phase transfer catalyst (PTC) (López-Fonseca et al 2008). Initially, a mixture of aqueous NaOH and solid-organic phase of PET is formed.…”
Section: Alkaline Hydrolysismentioning
confidence: 99%